Can a pulse oxygen saturation of 95% to 96% help predict further vital sign destabilization in school-aged children?: A retrospective observational study. Issue 25 (June 2018) - Kobayashi, Masaru; Fukuda, Shinya; Takano, Ken-ichi; Kamizono, Junji; Ichikawa, Kotaro
Abstract : Abstract: To determine whether a peripheral capillary oxygen saturation (SpO2 ) of 95% to 96% should be considered "nonurgent" in school-aged children, as suggested by the Canadian Emergency Department Triage and Acuity Scale. School-aged children (6–12 years old) with a normal body temperature (36.5–37.4°C) who visited our department between September, 2014 and August, 2015 (n = 4556) were divided into 4 groups based on SpO2 : group A: 99% to 100%; group B: 97% to 98%; group C: 95% to 96%; and group D: ⩽94%. The heart rate (HR), respiratory rate (RR), and hospitalization rate were compared among the groups, and also between children with SpO2 95% to 96% and matched controls with SpO2 ≥97% (n = 280 each). Among 4556 eligible patients, groups A, B, C, and D comprised 2700 patients (59.3%), 1534 patients (33.6%), 280 patients (6.2%), and 42 patients (0.9%), respectively. The median (interquartile range [IQR]) RR significantly increased with decreasing SpO2 (23 [20–25], 24 [20–26], 24 [23–30], and 30 [24–40] breaths/min in groups A–D, respectively; P < .001). Similarly, the median (IQR) HR significantly increased with decreasing SpO2 (93 [83–104], 98 [87–110], 107 [93–119], and 121 [109–137] bpm, groups A-D, respectively; P < .001). Group D had the highest annual hospital admission rate (18 cases/42 patients, 42.9%). Further, the HR and RR differed significantly between the cases (107 [93–119] bpm; 24 [23–30] breaths/min) and controls (96 [86–106] bpm; 24 [20–28] breaths/min, respectively) ( P < .001 and P = .02, respectively). An SpO2 of 95% to 96% among school-aged children should not be considered "nonurgent, " but rather a significant clinical situation that requires early review of HR and RR. Prompt interventions among this group of children will help prevent further destabilization of vital signs, which will, in turn, contribute to decreased healthcare costs.